Computer Aided Reverse Vaccinology: A Game-changer Approach for Vaccine Development - Srivastava, Poornima; Jain, Chakresh K. (Combinatorial Chemistry & High Throughput Screening, 2023)
One of the most dynamic approaches in biotechnology is reverse vaccinology, which plays a huge role in today's developing vaccines. It has the capability of exploring and identifying the most potent vaccine candidate in a limited period of time. The first successful novel approach of reverse vaccinology was observed in Neisseria meningitidis serogroup B, which has revolutionised the whole field of computational biology. In this review, we have summarized the application of reverse vaccinology for different infectious diseases, discussed epitope prediction and various available bioinformatic tools, and explored the advantages, limitations and necessary elements of this approach. Some of the modifications in the reverse vaccinology approach, like pan-genome and comparative reverse vaccinology, are also outlined. Vaccines for illnesses like AIDS and hepatitis C have not yet been developed. Computer Aided Reverse vaccinology has the potential to be a game-changer in this area. The use of computational tools, pipelines and advanced soft-computing methods, such as artificial intelligence and deep learning, and exploitation of available omics data in integration have paved the way for speedy and effective vaccine designing. Is reverse vaccinology a viable option for developing vaccines against such infections, or is it a myth? Vaccine development gained momentum after the spread of various infections, resulting in numerous deaths; these vaccines are developed using the traditional technique, which includes inactivated microorganisms. As a result, reverse vaccinology may be a far superior technique for creating an effective vaccine.
Keywords: epitope prediction